Influencing factors in the simulation of airflow and particle transportation in aircraft cabins by CFD. (January 2022) - Cao, Qing; Liu, Mingxin; Li, Xingyang; Lin, Chao-Hsin; Wei, Daniel; Ji, Shengcheng; Zhang, Tengfei (Tim); Chen, Qingyan
Abstract: To control the transport of particles such as the SARS-CoV-2 virus in airliner cabins, which is a significant concern for the flying public, effective ventilation systems are essential. Validated computational fluid dynamics (CFD) models are frequently and effectively used to investigate air distribution and contaminant transportation. The complex geometry and airflow characteristics in airliner cabins pose a challenge to numerical CFD validation. The objective of this investigation was to identify accurate and affordable validation processes for studying the airflow field and particulate contaminant distribution in airliner cabins during the design process for different ventilation systems. This study quantitatively evaluated the effects of ventilation system, turbulence model, particle simulation method, geometry simplification, and boundary condition assignment on airflow and particulate distributions in airliner cabins with either a mixing ventilation (MV) system or a displacement ventilation (DV) system calculated by CFD. The results showed that among four turbulence models, the standard k-ε, RNG k-ε, realizable k-ε and SST k-ω models, the prediction by the realizable k-ε model agreed most closely with the experimental data. Meanwhile, the steady Eulerian method provided a reasonable prediction of the particle concentration field with low computing cost. The computational domain should be simplified differently for the DV system and the MV system with consideration of the simulation accuracy and computing cost. For more accurate modeling results, the boundary conditions should be assigned in greater detail, taking into account the uniformity on the boundary. Highlights: Evaluation of various factors in the accuracy of CFD simulations. Factors include ventilation system, turbulence model, particle simulation method, geometric model, and boundary conditions. Comparison of CFD results with experimental data from the literature.